2017
DOI: 10.1177/0883911517744572
|View full text |Cite
|
Sign up to set email alerts
|

Effect of changes in the surface chemistry and topography of poly(2-hydroxyethyl methacrylate) on the in vitro attachment of human corneal epithelial cells

Abstract: The effects on cell adhesion induced by changes in the topography and chemistry of poly(2hydroxyethyl methacrylate) hydrogel surfaces were investigated in vitro using the human corneal epithelial cell line, HCE-T. Poly(2-hydroxyethyl methacrylate) surfaces with a lotusleaf-like topography and poly(2-hydroxyethyl methacrylate) surfaces with a flat topography, but functionalized with the cell-adhesive peptide sequence Arg-Gly-Asp, both enhanced attachment of HCE-T cells as compared to flat, non-functionalized po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 87 publications
(115 reference statements)
0
1
0
Order By: Relevance
“…Accordingly, there have been a number of methods developed to derivatize PLA surfaces to enhance or control their interactions with biomolecules and cells . These include plasma treatment, solvent swelling followed by polymer entrapment from solvent/nonsolvent mixtures, and adsorption or grafting of amphiphilic co-polymers. In many cases, the aim has been to promote attachment of eukaryotic cells so that the PLA matrix can act as a support for tissue growth, and multiple papers have shown that chemical functionalization of the biomaterial’s surface can enhance or reduce the interactions between varying cell types and substrates. …”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, there have been a number of methods developed to derivatize PLA surfaces to enhance or control their interactions with biomolecules and cells . These include plasma treatment, solvent swelling followed by polymer entrapment from solvent/nonsolvent mixtures, and adsorption or grafting of amphiphilic co-polymers. In many cases, the aim has been to promote attachment of eukaryotic cells so that the PLA matrix can act as a support for tissue growth, and multiple papers have shown that chemical functionalization of the biomaterial’s surface can enhance or reduce the interactions between varying cell types and substrates. …”
Section: Introductionmentioning
confidence: 99%